Modulation of plant ethylene levels by the bacterial enzyme ACC deaminase - Glick, Bernard R. (FEMS microbiology letters, 2005)
Soil microorganisms that produce the enzyme 1-aminocyclopropane-1-carboxylate (ACC) deaminase promote plant growth by sequestering and cleaving plant-produced ACC, and thereby lowering the level of ethylene in the plant. Decreased ethylene levels allows the plant to be more resistant to a wide variety of environmental stresses. Here, the biochemistry of ACC deaminase; the environmental distribution, regulation, evolution and expression of ACC deaminase genes; and information regarding the effect of this enzyme on different plants is documented and discussed.